Green finance, environmental regulation, and the optimization of industrial structure in China’s Yangtze River economic belt - Xiang, Jin; Tang, Decai; Zhou, Yunzhu; Chen, Qing (Frontiers in Environmental Science, 2025)
This paper focuses on the Yangtze River Economic Belt (YREB) in China as its research subject. It utilizes provincial data from 2005 to 2023, employing a regression analysis framework that incorporates green finance (GF) and environmental regulation (ER). Additionally, it explores these factors further using the panel threshold regression model and the spatial econometric model. The findings show that GF and ER apply a relatively significant positive influence on the advancement of the industrial structure but a significant inhibitory effect on the rationalization of industrial structure. Moreover, the impact on the upgrading of industrial structure is not significant, but it has a significant inhibitory effect on the rationalization of industrial structure when considering the interaction term of the two. The impact of GF and ER on industrial transformation exhibits a clear heterogeneity. As the intensity of ER grows, the promoting effect of GF on the upgrading of the industrial structure will weaken, while its inhibitory effect on the rationalization of the industrial structure will significantly increase. The impact of GF and ER on the optimization of industrial structures has a spatial spillover effect. Consequently, industrial transformation is influenced not only by the external constraints of ER but also by the indispensable financial support from GF. It is imperative for these two elements to collaborate synergistically. The study’s findings provide policy recommendations for optimizing the industrial structure of the YREB and lay the foundation for advancing the green industry and promoting sustainable economic development.